Cooperative-waqf model: a proposal to develop idle waqf lands in Malaysia - Allah Pitchay, Anwar; Mohd Thas Thaker, Mohamed Asmy; Mydin, Al Amin; Azhar, Zubir; Abdul Latiff, Abdul Rais (Emerald Publishing Limited, 2018)
Purpose – Waqf (Islamic endowment) in the form of cash is important to address the problem of developing idle waqf lands. Although there are various existing models of cash waqf, there is still a need for innovative cash waqf models. This paper aims to offer an alternative mode of financing for developing idle waqf lands using the concepts of cooperatives and waqf. Design/methodology/approach – The present study first evaluates relevant literature on financing issues faced by waqf institutions in developing idle waqf lands as well as existing models of cash waqf. Based on the prevailing gap in cash waqf models, the study proposes a hybrid model of cooperative-waqf to finance idle waqf lands in Malaysia. Findings – The proposed model is unique owing to the new dimension of membership being embedded into the waqf project. It considers donors as members of the waqf project, which is funded through the cash waqf collected, and thus, donors are given the privilege to receive benefits from the commercialised projects that are developed on the waqf lands. The existing models of cash waqf use traditional methods in which donors merely contribute cash waqf without any awareness of how the contributions are utilised. Usually, this problem occurs due to the lack of reciprocal communication between cash waqf donors and waqf institutions. Research limitations/implications – The present study examines the case of waqf land development in the context of Malaysia only. Secondly, the paper does not contain any empirical analysis, and the development of the paper is based on existing literature that discusses various models of cash waqf practised in Muslim-majority and -minority countries. Future research can conduct surveys of donors and other stakeholders on the practicality of the model. Practical implications – It is expected that the proposed cooperative-waqf model will be able to create a synchronised relationship between cash waqf donors and waqf institutions and hence boost participation in developing waqf lands. Originality/value – The present study adds to the existing literature in the area of waqf and cash waqf models, especially the application of this instrument in the context of Malaysia. It also offers a new hybrid model to the State Islamic Religious Councils (SIRCs) – Malaysia’s sole trustee of waqf assets management – such that the implementation of the proposed model could boost the collection of cash waqf in developing commercial projects on idle waqf lands.